Risk Factors for the Occurrence and Progression of Posttraumatic Elbow Stiffness: A Case-Control Study of 688 Cases - Qian, Yun; Yu, Shiyang; Shi, Yue; Huang, Hengye; Fan, Cunyi (Frontiers in Medicine, 2020)
Background: Elbow stiffness is a severe complication after trauma. Surgical or conservative treatments may be ineffective for restoring functional elbow motion. We aim to evaluate intrinsic and extrinsic factors for the occurrence and severity of elbow stiffness. Methods: This retrospective case-control study included mild/moderate stiffness, severe stiffness and non-stiffness groups between January 2011 and December 2017 at a single orthopedic center. Multivariable logistic regression analysis and subgroup analysis were used to evaluate age, gender, body mass index, muscle strength, fracture type and site, injury mechanism, immobilization time, elbow dysfunction time, multiple surgeries, nerve symptoms, physical therapy, smoking and alcohol abuse and dominant hand of stiff elbow as potential risk factors for the occurrence and severity of elbow stiffness. Results: There were 461 patients in the stiffness group and 227 patients in the non-stiffness group. The odds ratios (ORs) of the age, muscle strength, and injury mechanism were 0.960, 0.333, and 0.216 for the occurrence of elbow stiffness. In subgroup evaluation, increased cast immobilization time might be a risk factor for patients receiving conservative therapies (OR=2.02; p=0.014). In the evaluation on factors for progression of elbow stiffness, ‘multiple surgeries’ might be a risk factor in surgical treatment by subgroup analysis (OR=1.943; p=0.026). Nevertheless, alcohol abuse might increase severity of elbow stiffness in conservatively treated patients (OR=3.082; p=0.025). Conclusion: Increased cast immobilization time in the conservative therapy might be a risk factor for stiffness occurrence. Multiple surgeries might be risk factors for stiffness progression. Alcohol abuse potentially increased stiffness severity after conservative treatment.